Preparation of Novel Homodimers Derived from Cytotoxic Isoquinolinequinones. a Twin Drug Approach - Montoya-Kunsting, M; Ibacache-Rojas, J; Faundes-Anazco, J; Mejías-Medina, S (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
The synthesis of five novel homodimers is reported based on the anilinoisoquinolinequinone scaffold. In these twin-drug derivatives, two units of the anilinoquinone pharmacophores are linked through a methylene spacer. The formation of dimers was achieved by reaction of isoquinolinequinones with 4, 4’-diaminodiphenylmethane via a sequence of two oxidative amination reactions. A preliminary in vitro screening of the homodimers reveals moderate to high cytotoxic activities against MDA-MB-21 breast adenocarcinoma and B16-F10 murine metastatic melanoma cell lines. The asymmetrical homodimer 15 stands out due to its cytotoxic potencies at submicromolar concentrations and high selectivity index (mean IC50 = 0.37 μM; SI = 6.97) compared to those of etoposide (mean IC50 = 3.67; SI = 0.32) and taxol (mean IC50 = 0.35; SI = 0.91) employed as reference anticancer drugs. © 2018 by the authors.